An Application of an Information System via modern Topology - Salwa Ahmed Elsayed; Arafa Nassef; Mohammed Shokry; Abdallah Shalaby (Journal of Engineering Research - Egypt, 2022)
AbstractThis paper will discuss developing a new mathematical method through analysis ofinformation system where we deal with some ambiguity problems. We will representthis knowledge into one or more types of classes then we can use these classes to makea topology called modern Topology. After that we will compare the base of modernTopology with other basis after removing some attributes then we will decide the coreelements via the comparison. These elements will obviously be the true elements in the information system .we also will explain some analysis examples about diseases ,plantsand languages .we can show the core elements via methods of analysis .This paper shows how to use reduction of information through attribute reduction.After removing each attribute we must keep the basic properties of the system.This will inspire many to contribute to the cultivation of modern Topology in the field of mathematical instructure of modern approximations.partically rough set theory.